2004
DOI: 10.2169/internalmedicine.43.787
|View full text |Cite
|
Sign up to set email alerts
|

The Lower Pole of the Earlobe is an Alternative Site for Painless Blood Sampling in the Self-assessment of Blood Glucose Concentrations

Abstract: Objectives Measurement of blood glucose is essential for better control of diabetes mellitus. The pain associated with repeated blood sampling is a significant problem, and a less painful technique would be advantageous. This study was conducted to establish a less painful method of blood sampling for monitoring of blood glucose concentrations.Methods Fourteen healthy doctors and nurses at the age of 22 to 32 years were enrolled into this study. The earlobe was divided into 20 areas. Each area was punctured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…There is a considerable body of evidence suggesting that the earlobe is a less painful site than the finger for glucose testing (Carley et al, 2000;Shibata, Nurashige, & Kami, 2004;Toledo & Taylor, 2004) but little evidence to show a correlation of glucose concentrations, especially in a heterogeneous population. There is no evidence to show a correlation in hypoglycemic state.…”
Section: Background and Significancementioning
confidence: 99%
“…There is a considerable body of evidence suggesting that the earlobe is a less painful site than the finger for glucose testing (Carley et al, 2000;Shibata, Nurashige, & Kami, 2004;Toledo & Taylor, 2004) but little evidence to show a correlation of glucose concentrations, especially in a heterogeneous population. There is no evidence to show a correlation in hypoglycemic state.…”
Section: Background and Significancementioning
confidence: 99%
“…Shibata et al . () noted that the earlobe is also innervated with nociceptors and they concluded that pricking the lower part of the earlobe resulted in the least pain. Following this, the study nurse also asked the participant to rate the level of pain for the procedure on the Faces Pain Scale.…”
Section: The Studymentioning
confidence: 99%
“…Then, the study nurse obtained a blood sample for capillary blood glucose monitoring at the lower part of the earlobe, which was taken at the same side as the fingertip used for blood glucose monitoring. Shibata et al (2004) noted that the earlobe is also innervated with nociceptors and they concluded that pricking the lower part of the earlobe resulted in the least pain. Following this, the study nurse also asked the participant to rate the level of pain for the procedure on the Faces Pain Scale.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations